An obesogenic island in the Mediterranean: mapping potential drivers of obesity in Malta. Issue 17 (10th March 2015) - Cauchi, Daniel; Rutter, Harry; Knai, Cecile
Abstract: Objective: The prevalence of childhood and adult obesity in Malta is among the highest in the world. Although increasingly recognised as a public health problem with substantial future economic implications for the national health and social care systems, understanding the context underlying the burden of obesity is necessary for the development of appropriate counter-strategies. Design: We conducted a contextual analysis to explore factors that may have potentially contributed to the establishment of an obesogenic environment in Malta. A search of the literature published between 1990 and 2013 was conducted in MEDLINE and EMBASE. Twenty-two full-text articles were retrieved. Additional publications were identified following recommendations by Maltese public health experts; a review of relevant websites; and thorough hand searching of back issues of the Malta Medical Journal since 1990. Setting: Malta. Subjects: Whole population, with a focus on children. Results: Results are organised and presented using the ANalysis Grid for Elements Linked to Obesity (ANGELO) framework. Physical, economic, policy and socio-cultural dimensions of the Maltese obesogenic environment are explored. Conclusions: Malta's obesity rates may be the result of an obesogenic environment characterised by limited infrastructure for active living combined with an energy-dense food supply. Further research is required to identify and quantify the strength of interactions between these potential environmental drivers of obesity in order to enable appropriate countermeasures to be developed.